AN APPROACH OF FLOW MEASUREMENT IN SOLAR WATER HEATER USING TURBINE FLOW METER - Kolhare, N. R.; Thorat, P. R. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
boost its use in domestic applications. A Techno-economical system is designed using microcontroller based turbine flow meter to measure flow of water in solar water heater. There is no need of bulky remote electronics system. Here a turbine is inserted in the pipeline which rotates around its axis the speed of this rotation is directly proportional to the rate of flown. To measure the flow electronically through non-contact methodÂ Â one arm of the turbine can be made of a magnet and a Hall Effect device attached on the outer side of the pipe. The Hall Effect switch would pick up the passage of the magnetic arm and generates a pulse. By counting the number of pulses per second or minute depending on the speed of the turbine and the desired resolution (i.e. multiplication factor) the flow can be calculated.